A comparative study of the analgesic effects of piroxicam mefenamic acid and ibuprofen on post-operative dental pain - Kwan, Grace V.
Seventy-five Filipino subjects, 46 males and 29 females, with ages from 18 to 50 years (mean age: 26, 76 years), with no systemic illnesses were selected. Multiple tooth extractions (2 or more teeth) were done. Twenty five patients were given 500 mg. mefenamic acid. Another 25 were given 400 mg. ibuprofen while the rest were given 20 mg. piroxicam. The patients were given instruction to evaluate post extraction pain before drug intake and 1 hour, 4 hours, and 8 hours after drug intake. Pain evaluation forms were given to each patient and these were returned to be tabulated and analyzed. Results showed that there were no significant differences in the analgesic effects of the three drugs after 1 hour, 4 hours, and 8 hours.